2014
DOI: 10.1080/00071668.2013.871502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of danofloxacin in common pheasants, guinea fowls and Japanese quails after intravenous and oral administration

Abstract: 1. The pharmacokinetics of danofloxacin was investigated in common pheasants, guinea fowls and Japanese quails after intravenous (i.v.) and oral (p.o.) administration at a dose of 10 mg kg(-1) body weight. Concentrations of the drug in serum were determined by high-performance liquid chromatography. The values of the pharmacokinetic parameters after both applications were calculated on the basis of a one-compartment model. 2. The elimination half-lives after i.v. injection were 6.82 ± 1.87, 3.31 ± 0.13 and 3.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 21 publications
7
18
1
Order By: Relevance
“…And their values were 0.31 ± 0.03 and 0.11 ± 0.02 L/h/kg, respectively, which indicated that the total body clearance (Cl tot ) of danofloxacin was 0.42 L/h/kg in the present healthy model. The Cl tot presented here was close to those reported in Pheasant (0.45 ± 0.07; Dimitrova et al ., ) and turkeys (0.59 ± 0.14 L/h/kg; Haritova et al ., ), but slower than those in Japanese quail (1.61 ± 0.14 L/h/kg; Dimitrova et al ., ; 1;.48 ± 0.17 L/h/kg; Haritova et al ., ), and Guinea fowl (1.23 ± 0.07 L/h/kg; Dimitrova et al ., ). In the present infected model, the Cl re and Cl he were 0.41 ± 0.06 and 0.13 ± 0.05 L/h/kg, respectively, which were both faster than that in healthy model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…And their values were 0.31 ± 0.03 and 0.11 ± 0.02 L/h/kg, respectively, which indicated that the total body clearance (Cl tot ) of danofloxacin was 0.42 L/h/kg in the present healthy model. The Cl tot presented here was close to those reported in Pheasant (0.45 ± 0.07; Dimitrova et al ., ) and turkeys (0.59 ± 0.14 L/h/kg; Haritova et al ., ), but slower than those in Japanese quail (1.61 ± 0.14 L/h/kg; Dimitrova et al ., ; 1;.48 ± 0.17 L/h/kg; Haritova et al ., ), and Guinea fowl (1.23 ± 0.07 L/h/kg; Dimitrova et al ., ). In the present infected model, the Cl re and Cl he were 0.41 ± 0.06 and 0.13 ± 0.05 L/h/kg, respectively, which were both faster than that in healthy model.…”
Section: Discussionmentioning
confidence: 99%
“…K a was calculated using our previously reported danofloxacin concentrations in plasma in healthy chickens (Zeng et al ., ), whose value was 4.06 h −1 . For Cl re and Cl he, both were assumed to be 0.3 L/h/kg according to the reports in other birds (Haritova et al ., ; Dimitrova et al ., ), while the average (2.55) of P lu and P m (Table ) was set as that for P r because all of these three tissues were noneliminating ones. In addition, the starting value for K gic was assumed to be 1.0 h −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluoroquinolones have been widely employed in veterinary medicine because of their bactericidal effects against a broad range of pathogens (Davis, Papich, & Weingarten, ). These drugs act by preventing DNA supercoiling through the inhibition of bacterial DNA gyrase (Dimitrova, Haritova, Dinev, Moutafchieva, & Lashev, ). The pharmacokinetics of several fluoroquinolones have previously been reported in fish species, including difloxacin in gibel carp (Cao, Zhang, He, Zheng, & Yang, ), sarafloxacin in crucian carp (Fang, Zhou, & Liu, 2016b), and enrofloxacin in grass carp (Xu, Wang, Yang, & Lu, ), Nile tilapia (Teles, Branco, Del Bianchi, Pilarski, & Reyes, ), snakehead fish (Fang et al., ), and crucian carp (Fan et al., ).…”
Section: Introductionmentioning
confidence: 99%